2010
DOI: 10.1002/pd.2475
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester assessment of placenta function and the prediction of preeclampsia and intrauterine growth restriction

Abstract: Preeclampsia and intrauterine growth restriction (IUGR) are major contributors to perinatal mortality and morbidity worldwide. Both are characterized by impaired trophoblastic invasion of the maternal spiral arteries and their conversion from narrow muscular vessels to wide non-muscular channels. Despite improvement in the understanding of the pathophysiology of these conditions, ability to accurately identify pregnant woman who will develop them is limited. This greatly impairs the development and testing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 133 publications
5
87
0
2
Order By: Relevance
“…Increased impedance to blood flow in the uterine arteries as shown by a pulsatility index (PI) above the 95th percentile -frequently associated with pregnancy complications associated with defective trophoblast invasion -(36, 37) was observed in all women during Doppler assessment of uteroplacental perfusion (Tables 1 and 2, and Figure 1). Presence of diastolic notching (a characteristic waveform indicating decreased early diastolic flow) in the uterine artery reflects low vessel elasticity (37). Bilateral diastolic notching in uterine arteries was observed in 7 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Increased impedance to blood flow in the uterine arteries as shown by a pulsatility index (PI) above the 95th percentile -frequently associated with pregnancy complications associated with defective trophoblast invasion -(36, 37) was observed in all women during Doppler assessment of uteroplacental perfusion (Tables 1 and 2, and Figure 1). Presence of diastolic notching (a characteristic waveform indicating decreased early diastolic flow) in the uterine artery reflects low vessel elasticity (37). Bilateral diastolic notching in uterine arteries was observed in 7 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have revealed side-to-side differences in uteroplacental Doppler flow in pregnancies with unilateral placentas as well as the relationship between abnormal Doppler measurements and pre-eclampsia (13)(14)(15)(16)(17)(18)(19)(20)(21). However, reports on the direct association between placental location and development of pre-eclampsia, regardless of confounding factors (22), are limited.…”
Section: Introductionmentioning
confidence: 95%
“…In the attempt to improve the performance of the uterine artery as a screening test, new algorithms that take into account the maternal characteristics, history and/or biochemical markers have been proposed. In fact, uterine artery Doppler in the first and second trimester, in combination with several biochemical markers, has been extensively tested as a predictive test for preeclampsia and IUGR, and the first results are encouraging (Nicolaides 2006;Parra 2005;Plasencia 2007;Spencer 2007;Zhong 2010). Nevertheless, at present the literature comprises several large uncontrolled cohort studies and as yet there are no randomised studies in this field, and the cost-effectiveness remains to be proven.…”
Section: Description Of the Interventionmentioning
confidence: 99%